Implementation of Inclusive Education Policy: Study of Handling Student with Autism Spectrum Disorder (ASD) in Elementary School - Sonya Sinyanyuri; Arita Marini; Linda Zakiah (JIP Jurnal Ilmiah PGMI, 2024)
This research aims to describe the implementation of inclusive education policies for children with Autism Spectrum Disorder (ASD). This research is a narrative type qualitative research, data collection is carried out by interviewing class teachers, Special Assistant Teachers (GPK), GPK coordinators, and school principals at the Lazuardi GCS Elementary School in Depok City, observing, and reviewing documents. The data collection techniques used are interviews, observation, documentation, and Focus Group Discussion (FGD). Data analysis is applied through thematic analysis and content analysis. Testing the validity of the data is carried out by testing credibility through member checking to find out how far the data obtained is in accordance with what is stated. provided by the data provider, The research results show that this school has implemented an inclusive education policy by serving various children with special needs including ASD using a combination of Applied Behavior Analysis (ABA) and DIR-Floortime approaches to understand and change a person's behavior while DIR-Floortime an approach to emotional development through play activities. The supporting factors needed in handling ASD are the availability of good teachers, facilities, policies, assessment techniques, and parental support. The challenge in handling ASD in inclusive schools is the provision of resources and training to maintain competent teachers and all stakeholders in implementing inclusive education for children with ASD.